Exploring the potential of blockchain technology within the fashion and textile supply chain with a focus on traceability, transparency, and product authenticity: A systematic review - Badhwar, Aayushi; Islam, Saniyat; Tan, Caroline Swee Lin (Frontiers in Blockchain, 2023)
This paper provides a systematic review of the potential of Blockchain Technology within the fashion and textile industry’s supply chain to analyse its role in traceability, transparency, and product authenticity. To achieve this, a total of 152 research papers and non-scholarly resources have been scrutinised. An emphasis was placed on topics regarding Blockchain Technology (BT), the fashion and textile industry and supply chain (manufacturing and distribution), traceability, transparency, and product authenticity. The selected research papers range from empirical analysis, argumentative, case studies, opinion articles, review articles, short reports, and book chapters. Blockchain Technology has shown tremendous potential to be a foundation for the currently shifting paradigm towards more traceable and transparent supply chains. This review highlights the opportunities that exists in adapting Blockchain Technology in the fashion and textile supply chain. While also providing insight on the challenges in adopting the technology within the existing business infrastructure.